Integrating Islamic finance principles and the digital disruptive age to support global sustainability - Mahfudz, Akhmad Affandi; Rusyda Afifah Ahmad; Daribayeva Meruyert; Nafi Ilman Husin (Universitas Negeri Surabaya, 2024)
To support global sustainability, the integration of Islamic financial principles in the digital era can be a driver of a more just, inclusive, and sustainable financial system. It will also ensure economics equality in the country and promote the public financial ecosystem and the environment. The objective of this study is to evaluate the level of significance in incorporating the tenet of Shariah amid digital disruption in financial technology to support global sustainability by way of considering the element of environmental, economic and sustainability measures. This paper employs a qualitative that includes a strong pedigree on various databases and reputable journal local and abroad. The paper finds that the principle of Shariah can eliminate the practice of social and economic inequality by preventing economics activities that lead to injustice and oppression and ensuring that risk is shared equally in all transactions.